ANALISIS PERBAIKAN WORK STATION PADA PROSES PRODUKSI GARMENT DENGAN MENGGUNAKAN PENDEKATAN ENVIRONMENT ERGONOMIC - Rasyid, Mentari; Surachman, Surachman; Sugiono, Sugiono (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2016)
ABSTRACT Â Productivity garment greatly influenced by the work station facilities and presence in the workplace. UD Aliya- Malang is one example as an object of research. Based on the results of the initial surveys and interviews conducted by the operator, there are a number of complaints were found among them is the problem of the narrow room, the buildup of working materials at the work station, lighting and air circulation is less to make the operator comfortable in work. Based on the results of measurements, conditions of work station at UD Aliya still less ergonomic, which if left unchecked can lead to many complaints and problems in the future. Improvement of Â work station using Ergonomic Environment approach, the results can be obtained using the optimal amount of light for each work station, a reduction in noise levels, and improved air circulation using venilator turbine. As well as using ARC analysis, the results obtained are placement work station layout, the result is important juxtapose work station I and IV with the Warehouse.Â Keywords: Work Station, Activity Relationship Diagram, Environment Ergonomic